Community Structure of Eukaryotic Phytoplankton in Wetland of Golmud River and Its Lower Reaches and Relative Environmental Factors - Xiaoqi Dong; Huan Zhu; Xiong Xiong; Guoxiang Liu (Diversity, 2022)
Identification of the community structure of phytoplankton is an important link in studying the structure and function of aquatic ecosystems. However, research on the community structure of phytoplankton in the Golmud area is very scarce at present. To explore the composition of phytoplankton in the Golmud area, eukaryotic phytoplankton and environmental parameters were sampled in September 2020. The composition and diversity of the eukaryotic phytoplankton community were determined by microscopic observation and Illumina high-throughput sequencing technology. The results showed that a total of 40 species of eukaryotic phytoplankton from 4 phyla were identified by microscopic observation, and 154 species of eukaryotic phytoplankton from 7 phyla were obtained by high-throughput sequencing, mainly Bacillariophyta and Chlorophyta. The dominant species were Dunaliella sp., Teleaulax sp., Parvodinium mixtum, and Lindavia radiosa. The eukaryotic phytoplankton density in summer was 0.09–12.08 × 105 cells/L, the total biomass was 0.002–0.55 mg/L, and the concentration of chlorophyll-a was 0.00–0.91 μg/L. Multiple α diversity indices showed that the diversity of water in different salinities was in the order of freshwater > brackish > saline. The β diversity results showed that the eukaryotic phytoplankton community composition was more similar in water with the same salinity. The redundancy analysis results of water with different salinities showed that environmental factors susc as salinity, total phosphorus concentration, and dissolved oxygen affected the eukaryotic phytoplankton community structure, among which salinity had the greatest influence.